The Extension of Short-time Work Schemes during the Great Recession: A Story of Success? - Matthias Sebastian Hertweck; Björn Brey (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper evaluates the effectiveness of short-time work [STW] extensions - e.g. relaxing eligibility criteria or implementing new STW schemes - in the OECD during and after the Great Recession. First, we find that the dampening effect of STW on the unemployment rate diminishes at higher take-up rates. Second, only countries with preexisting STW schemes were able to fully exploit the benefits of STW. Third, the effects of STW are strongest when GDP growth is deeply negative at the beginning of recessions. Our results indicate that STW is most effective when used as a fast-responding automatic stabilizer.
Keywords: E24; J23; J68; 330